Digital transformation of healthcare and medical education, within, and beyond pandemic COVID-19 - Mohd Faeiz, Pauzi; Siti Norazlina, Juhari (2020)
Digital transformation during the pandemic COVID-19 has been impressive. Some organizations have accelerated the adoption of new technology and digitalization as their response to the pandemic COVID-19. The healthcare and medical education systems are also not left behind in adapting to new digital solutions. Examples include e-health and virtual consultations, management of big data and application of artificial intelligence, and the Internet of Things. The response in education includes remote learning and using educational technologies to empower medical graduate teaching. New ways of work using technologies and digital solutions not only beneficial within the unprecedented crisis but shine a light towards greater digital adoption beyond the pandemic COVID-19.